The Impact of Obesity on Dysmenorrhea and Lower Urinary Tract Symptoms in Adenomyosis Patients - Anggraeni, Asih; Insan Ksyatria, Yudhistya Ngudi; Baidlowi, Akhmad Ikhwan (Jurnal Kedokteran Brawijaya, 2024)
Obesity poses a substantial health challenge globally, affecting various aspects of reproductive health, including adenomyosis. Adenomyosis, characterized by the presence of endometrial tissue within the myometrium, commonly affects women during their reproductive years, leading to symptoms such as dysmenorrhea and lower urinary tract symptoms (LUTS). This study aimed to investigate the influence of obesity on dysmenorrhea and LUTS severity in adenomyosis patients, considering demographic factors such as age and educational levels as potential moderators. Forty-four adenomyosis patients participated in a cross-sectional study at Dr. Moewardi General Hospital in Surakarta City of Indonesia, between April and September 2023. Diagnosis was confirmed using 2D Transvaginal Ultrasound (2D-TVUS). Obesity was defined using Body Mass Index (BMI) categories, and dysmenorrhea and LUTS were assessed using the Numerical Rating Scale (NRS) and modified International Prostate Symptom Score (IPSS) questionnaire, respectively. Statistical analyses included Pearson correlation. Results indicated a significant positive correlation between obesity and dysmenorrhea (rho = 0.256, P = 0.049) and LUTS (rho = 0.292, P = 0.029). Age and educational level did not significantly moderate these relationships, emphasizing the independent influence of obesity on symptom severity. In conclusion, obesity significantly impacts the severity of dysmenorrhea and LUTS in adenomyosis patients, highlighting the need for tailored management strategies that address both hormonal and inflammatory pathways.